The ecological library science: a necessary change in Costa Rican libraries - Ugalde Víquez, Aracelly (2015)
This research is a novel knowledge about the library contribution because it proposes to create a new branch discipline the "green library". Analysis is a proposal from the college to address before the society and academia collective experience accumulated by the Costa Rican specialized libraries in these areas throughout their years of service and information management practices using front to the country's needs.Costa Rica is a country with a broad global recognition in the ecological theme and ecotourism, for the vast territories are protected areas for the preservation of ecological diversity, among others.The objective of this research was to demonstrate the importance of information management environment in libraries, proposing a new discipline: the ecological library. In addition, the contributions of the documentation centers and libraries specializing in this subject, in Costa Rica "were identified. The environmental management concept chosen for this research considering the importance of science librarianship as expand its disciplinary areas, to study specialties linked to national development.Currently, the document management aimed at providing information services on the current reality and aimed towards priority areas such as environmental management, climate change adaptation, and housing, employment, transparency and risk reduction. The role of documentation centers and libraries and information professionals is important, because they must be instances advice in making political, economic, social decisions that guarantee safeguarding the short and long term of our environmental history, and accessibility of information on this subject. In addition, they have to be able to create ecological culture, implement procedures to ecological literacy and "dating" communities for all human beings, we protect the environment.This research considered unique in its kind and a pioneer in this field in Costa Rica; it is a study of mixed approach and three sources of information consulted:1. The library staff consists of 24 officials of 24 specialized libraries and documentation centers selected for their functions and the contents of their collections.2. The virtual visibility projecting these 24 libraries in national and international networks.3. Public opinion on the contribution of these libraries to the environment.The first population was applied descriptive research, to gather information from the survey and a questionnaire consisting of 15 variables. Qualitative research used in the second source of information about the virtual visibility of libraries and public opinion gathered using an exploratory study, another survey conducted by social networks.